Концепция нового социального конфликта Алена Турена - Казаков, В. (Социология: теория, методы, маркетинг, 2008)
The paper comprehensively analyzes the approach to a problem of a new social conflict suggested by the well-known French sociologist Alain Touraine. According to A. Touraine’s ‘sociology of action’, the substance of conflict at the macrolevel comes through implementation of historicity, or a society’s ability to construct it self using a set of sociocultural patterns. The essence of a new conflict is not expressed through a fight for justice, freedom, brotherhood or equal rights any more. It lies in the struggle for happiness as a general inner feeling of satisfaction. Generally, the Authority and the Human be come key actors of a new conflict. Its distinctive features, such as totality, expanding scope, diffuse and permanent nature, constructedness, de-institutionalization and ubiquity determine individualized, spontaneous and recurrent character of conflict in all spheres of social life. This is a collective-supported struggle of every one for all — against administrative machinery and any form of domination, even against established norms and rules. At the mesolevel, conflict manifests it self in the form of new social movements considered as direct conflict actions. Those movements do not support any ideology or power struggle (like working class movement at an earlier time). They are neither related to any political organizations nor help to win popular vote. In stead of this, new social movements declare certain ideas, values, and goals meeting with approval among most people. At the microlevel, conflict is mirrored in a research technique of sociological intervention that firstly implies in-depth study of small social groups and behavior of their members over a long period of time.